(untitled) (Veterinary Science, 2017)
Parasitic myelopathy by Gurltia paralysans is, apparently, a South American disease, but little is known about it. It is a medullary disorder caused by a parasite that in its adult form, it is lodged in the spinal veins of cats causing a hemorrhage by suffusion that compromises the spinal cord in a variable way. It has been proposed that domestic cats are accidental guests, and that small wild cats such as the huiña cat (Felis guigna) in Chile, or the cat of the pampas (Felis geoffroyi) in Brazil and Argentina, are the definitive hosts, housing the parasite in the lung. Cats are likely infected by ingesting small lizards. The affected animals present typical signs of chronic myelopathy, with varying degrees of affection, from ataxia to severe paraparesis, depending on the time of evolution. The main lesions are between T10 and L2, with projection up to L5-L6. The affected cats always live in rural areas, and this parasitosis has not been diagnosed in any urban area. The diagnosis is based on the clinical history of slowly progressive chronic myelopathy and the habitat of sick cats. Recently a PCR technique has been developed that allows the identification of parasitic DNA in the CSF of the affected cats. The treatment is based on the application of ivermectin, and it is most effective if it is implemented early.